86. Onabotulinumtoxin-A treatment in chronic migraine with medication overuse: A two years Italian experience. Issue 12 (December 2017) - Butera, C.; Colombo, B.; Bianchi, F.; Amadio, S.; Guerriero, R.; Tronci, S.; Cursi, M.; Comi, G.; Del Carro, U.
Abstract : Onabotulinumtoxin-A (BT-A) is an authorised prophylactic therapy in chronic migraine (CM). Its efficacy has been proved by both clinical trials and observational studies. Few data are still available on the efficacy of BT-A injection and the most adequate treatment interval after the first year of follow-up. This study aimed to verifyefficacy, safety and the most adequate timing of BT-A injections in CM patients during the second year of treatment. we evaluated 20 CM patients with medication overuse MO (17 females and 3 males) treated with BT-A for 24 months. After the fourth treatment, we decided to retreat responder patients based on their clinical result. Main efficacy variables were registered at each visit, including days of headache/migraine, total cumulative headache hours, MIDAS and HIT-6 scores, together with symptomatic drugs intake. All variables at week 24 maintained the improvement evidenced at week 12. Adverse events were rare and did not require treatment discontinuation. Most of the patients ( n  = 13) continued to perform trimestral injections, 5 patients every 4 months and 2 patients every 6 months. BT-A in CM patients is effective even after two years of treatment when administered with an individualised interval according to the clinical outcome.